1995
DOI: 10.1006/cogp.1995.1011
|View full text |Cite
|
Sign up to set email alerts
|

Cataphoric Devices in Spoken Discourse

Abstract: We propose that speakers mark key words with cataphoric devices. Cataphoric devices are counterparts to anaphoric devices: Just as anaphoric devices enable backward reference, cataphoric devices enable forward reference. And just as anaphoric devices mark concepts that have been mentioned before, cataphoric devices mark concepts that are likely to be mentioned again. We investigated two cataphoric devices: spoken stress and the indefinite this. Our experiments demonstrated three ways that concepts marked by ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
3
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 45 publications
6
70
3
2
Order By: Relevance
“…One possibility is that there is a general mechanism such that readers continually adjust the amount of processing devoted to each text input on the basis of its perceived importance, or salience. This is consistent with the findings that text in the focused portion of a sentence is remembered better (e.g., Gernsbacher & Jescheniak, 1995) and that readers are more likely to detect errors in text that is linguistically focused (e.g., Bredart & Docquier, 1989). These findings suggest that linguistic focus serves as a cue to readers to process the information more thoroughly.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…One possibility is that there is a general mechanism such that readers continually adjust the amount of processing devoted to each text input on the basis of its perceived importance, or salience. This is consistent with the findings that text in the focused portion of a sentence is remembered better (e.g., Gernsbacher & Jescheniak, 1995) and that readers are more likely to detect errors in text that is linguistically focused (e.g., Bredart & Docquier, 1989). These findings suggest that linguistic focus serves as a cue to readers to process the information more thoroughly.…”
supporting
confidence: 86%
“…Syntactic focus has been manipulated with whquestions (e.g., Birch & Rayner, 1997;Cutler & Fodor, 1979), it cleft constructions (e.g., Birch & Garnsey, 1995;Morris & Folk, 1998), and subordinate versus main clauses (e.g., Baker & Wagner, 1987). These linguistic focusing devices have been found to lead to better memory for the focused portion of the sentence (e.g., Gernsbacher & Jescheniak, 1995) and longer reading times (e.g., Birch & Rayner, 1997;Carpenter & Just, 1977). Moreover, in a story continuation task, Birch et al (2000) found that readers were more likely to refer to concepts from earlier in the story if they had been syntactically focused than if they had not, suggesting that syntactic focus serves to increase the accessibility of the focused concepts as well as to increase readers' expectations that these concepts will continue to be prominent in the story.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our paper suggests one central reason for the comparability of metaphor and literal comprehension: They are understood via exactly the same general comprehension mechanisms. Specifically, we demonstrated that the same mechanisms of enhancement and suppression that underlie comprehension in general (e.g., Gernsbacher & Faust, 1991a) and language comprehension in particular (e.g., Gernsbacher & Jescheniak, 1995;), are also crucial for metaphor understanding. Our findings suggest that metaphor comprehension could be naturally accounted for within the Structure Building Framework (Gernsbacher, 1990;1991a;1995;1997c).…”
Section: Comprehension Mechanisms and Metaphor Understandingmentioning
confidence: 85%
“…Suppression is the active reduction in activation of activated memory nodes that represent information that is potentially confusing or irrelevant for comprehension. Gernsbacher and her colleagues have demonstrated the role of these two mechanisms in lexical access (e.g., Gernsbacher & Faust, 1991b;Gernsbacher & St. John, in press), anaphora (e.g., Gernsbacher, 1989;1997a), cataphora (e.g., Gernsbacher & Jescheniak, 1995;Gernsbacher & Shroyer, 1989), as well as the comprehension of non-linguistic information (e.g., Gernsbacher & Faust, 1991a).…”
Section: Comprehension Mechanisms and Metaphor Understandingmentioning
confidence: 99%